Vittorio Alfieri's Panegyric of Pliny to Trajan: Critical Reconnaissance and New Perspectives (ACME, 2024)
This paper presents a critical recognition of Vittorio Alfieri’s Panegirico di Plinio a Trajano from the early decades of the 20th century to the 2000s. The work was long considered as a literary exercise, and it was only from the 1980s onwards, thanks to Giuseppe Rando’s studies, that its political and historical value within Alfieri’s work was recognised. This study will therefore attempt to offer an overview of the criticism of the work, analysing the evolution of studies on the Panegirico and finally highlighting new perspectives and research paths that have not yet been fully investigated.
Keywords: Vittorio Alfieri; Panegirico di Plinio a Trajano; Giuseppe Rando; Eighteenth century; History of literary criticism